2009
DOI: 10.1007/s11199-008-9571-7
|View full text |Cite
|
Sign up to set email alerts
|

Equality Discrepancy Between Women in Same-Sex Relationships: The Mediating Role of Attachment in Relationship Satisfaction

Abstract: This internet study explored the mediating effects of anxious and avoidant attachment on the link between relationship equality discrepancy and relationship satisfaction among 75 cohabitating U.S. and Canadian women's same-sex couples. Multiple regression results indicated that both anxious and avoidant attachment were found to mediate the relationship between dyadic equality discrepancy and relationship satisfaction, suggesting that the more partners perceived their relationships to be unequal, the more indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…While the centrality of gender to sexual satisfaction has been previously explored, researchers have often focused on gender ideals and gender norm conformity (Horne and Bliss, 2009;Sanchez et al, 2012) rather than positive or satisfying aspects of femininity and masculinity. For example, examined individuals' conformity to gender ideals (the ''ideal woman'' or ''ideal man'') and found that investment in gender conformity predicted lower sexual satisfaction.…”
Section: Gendermentioning
confidence: 99%
“…While the centrality of gender to sexual satisfaction has been previously explored, researchers have often focused on gender ideals and gender norm conformity (Horne and Bliss, 2009;Sanchez et al, 2012) rather than positive or satisfying aspects of femininity and masculinity. For example, examined individuals' conformity to gender ideals (the ''ideal woman'' or ''ideal man'') and found that investment in gender conformity predicted lower sexual satisfaction.…”
Section: Gendermentioning
confidence: 99%
“…The role of power and relationship satisfaction has received considerable research attention in female same-sex relationships (e.g., Caldwell & Peplau, 1984;Horne & Biss, 2009;Kurdek, 1998;Peplau, Padesky, & Hamilton, 1983); WSW who report a balance of power in their relationships also report higher relationship satisfaction (e.g., Eldridge & Gilbert, 1990;Kurdek, 2003). In spite of this, only one questionnaire study of 77 women who were in "romantic/sexual" same-sex relationships has looked at power and sexual satisfaction (Caldwell & Peplau, 1984) finding that those who reported an equal balance of power between partners in the relationship also reported greater sexual satisfaction.…”
Section: Sexual and Relationship Therapy 385mentioning
confidence: 99%
“…Third, comothers in same‐sex couples are more likely to confront competition with each other during parenthood than cofathers in same‐sex couples, as partners in same‐sex female couples place more emphases on role equality and sensitivity to (un)fairness in relationships (Horne & Biss, ; Kurdek, ). Perhaps as a result, comothers in same‐sex couples report a higher likelihood of engaging in conflicts induced by asymmetrical legal, biological, and emotional bonds with children than do cofathers in same‐sex couples (Pelka, ).…”
Section: Sexual Minority Parental Identities In a Heteronormative Socmentioning
confidence: 99%
“…Given that same‐sex couples (particularly female couples) tend to place more emphasis on fairness and equality within the relationships than do heterosexual couples (Dunne, ; Goldberg, ; Horne & Biss, ; Kurdek, ), an increased specification of labor between partners during the transition to parenthood may be more likely to induce tension, conflicts, and distress for couples. New same‐sex coparents may need to develop strategies to offset the potentially negative effects of the disproportionate share of child care and housework.…”
Section: Sexual Minority Parental Identities When Renegotiating Divismentioning
confidence: 99%
See 1 more Smart Citation